Political power and corporate control: the new global politics of corporate governance. - Gourevitch, Peter A; Shinn, James (Princeton University Press, 2010)
Why does corporate governance--front page news with the collapse of Enron, WorldCom, and Parmalat--vary so dramatically around the world? This book explains how politics shapes corporate governance--how managers, shareholders, and workers jockey for advantage in setting the rules by which companies are run, and for whom they are run. It combines a clear theoretical model on this political interaction, with statistical evidence from thirty-nine countries of Europe, Asia, Africa, and North and South America and detailed narratives of country cases.